Microwave processing of ores - Giyani, Baker (2023)
Copper is a widely used metal in applications ranging from electronics to building and construction. The demand for copper has increased more rapidly in recent years due to technological advancements, industrial development, and population growth. This is set against a backdrop where the global copper head grade is dropping because higher-grade ore bodies are already mined or becoming exhausted. This means that larger volumes of low-grade ores are being processed in plant operations to keep up with the growing demand. However, processing these low-grade ores using existing flowsheets is unlikely to be sustainable due to enhanced energy consumption and low process efficiency. Thus, innovative processing technologies must be explored to treat such ores if mineral processing is ever to become sustainable. Microwave treatment of ores is one such processing technology that has been demonstrated to reduce ore competency and improve mineral liberation by inducing intergranular and transgranular fractures. Both these outputs, of course, leading to reduced energy consumption and higher process efficiency. The principal mechanism of microwave-induced fractures in ores is based on differential thermal stresses generated through rapid and selective heating of microwave-absorbent phases (e.g., sulphide minerals) within a microwave-transparent gangue matrix (rock-forming minerals). In hydrometallurgical processes, the induced fractures expose more sulphide grains to the leach solution, improving mass transfer and enhancing metal leach recovery. It has also been shown that a candidate ore should have suitable mineralogy and texture properties in order to support the creation and the effective transfer of induced stresses to enable crack propagation.